The Role of Domain Content in Understanding Identity Development Processes. (27th September 2014) - McLean, Kate C.; Syed, Moin; Yoder, Alisha; Greenhoot, Andrea F.
Abstract : The current studies examined the importance of domain content in the processes of identity development using two approaches—narrative and status. We examined personal narratives for identity domain content, the co‐occurrence of different contents, and the relations between content and processes, using two approaches to identity—status and narrative. Across two studies, 762 participants (average age = 19 years) and 2214 narratives, traditional ideological and interpersonal status domains were present, but so was a novel domain: existential concerns. Narrative identity processes were more frequent in narratives with multiple contents, and relations between identity statuses processes and narrative processes were modest. We discuss theoretical implications, the importance of examining content, and the utility of narrative approaches for doing so.